160k views
3 votes
(csc x - 1) (csc x + 1)

1 Answer

3 votes

Step-by-step explanation:

Here we have the following expression:


(csc x - 1) (csc x + 1)

So we need to extend this. Remember that the difference of squares tells us:


(a-b)(a+b)=a^2-b^2

So here:


a=cscx \\ \\ b=1

Thus:


(csc x - 1) (csc x + 1)=csc^2x-1 \\ \\ \\ But: \\ \\ cscx=(1)/(sinx) \\ \\ \\ Then: \\ \\ csc^2x-1=(1)/(sin^2x)-1=(1-sin^2x)/(sin^2x)=(cos^2x)/(sin^2x)=cot^2x \\ \\ \\ Finally: \\ \\ \boxed{(csc x - 1) (csc x + 1)=cot^2x}

User Esau
by
5.5k points